2017
DOI: 10.1038/ncomms15081
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA-seq enables comprehensive tumour and immune cell profiling in primary breast cancer

Abstract: Single-cell transcriptome profiling of tumour tissue isolates allows the characterization of heterogeneous tumour cells along with neighbouring stromal and immune cells. Here we adopt this powerful approach to breast cancer and analyse 515 cells from 11 patients. Inferred copy number variations from the single-cell RNA-seq data separate carcinoma cells from non-cancer cells. At a single-cell resolution, carcinoma cells display common signatures within the tumour as well as intratumoral heterogeneity regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
791
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 840 publications
(827 citation statements)
references
References 61 publications
32
791
2
2
Order By: Relevance
“…1d). This predominant grouping of cancer cells by their tumor of origin has been reported for a number of cerebral and non-cerebral tumors [11,14,33,37,50,54,61]. For identifying traits common to all tumors, data can be analyzed tumor per tumor [62,63,69], or merged and analyzed as a whole after standardization (i.e.…”
Section: Unsupervised Clustering Analysis Highlights First Gbm Cells'mentioning
confidence: 71%
“…1d). This predominant grouping of cancer cells by their tumor of origin has been reported for a number of cerebral and non-cerebral tumors [11,14,33,37,50,54,61]. For identifying traits common to all tumors, data can be analyzed tumor per tumor [62,63,69], or merged and analyzed as a whole after standardization (i.e.…”
Section: Unsupervised Clustering Analysis Highlights First Gbm Cells'mentioning
confidence: 71%
“…Further, by identifying genes that were most often co-expressed, the authors identified several “hub” genes coordinating the most common gene expression profiles identified in the cells, including genes such as SCN2A, CENPH , TUBGCP2 , LINC00189 , and ARHGAP15 , encompassing genes both known and previously unknown to have cancer involvement. Chung and colleagues performed single cell RNA-sequencing of cells from 11 patients with various breast cancer subtypes to identify heterogeneity of subtypes even among cells from the same patient tumor and to pinpoint subtype-specific differences in gene expression [55]. Specifically, the group found that TNBC cells have increased expression of epithelial-to-mesenchymal transition (EMT) genes than luminal and HER2+ cells, and that gene expression varies widely in cells of the TNBC subtype.…”
Section: Tumor Heterogeneity Exists At Multiple -Omic Levelsmentioning
confidence: 99%
“…Single-cell analysis is a recently developed systematic method used to evaluate the heterogeneity of a cell population. 20,21 In the present study, we used single-cell gene expression analysis on stem cell-and gastric cell lineage-markers and evaluated features of drug-tolerant persister cells in gastric cancer patient-derived cells (PDC). Through this analysis, we identified a potential therapeutic target pathway of gastric cancer persister cells.…”
Section: Introductionmentioning
confidence: 99%